Complementing the Sculpting Metaphor: Reflections on How Relationship Partners Elicit the Best or the Worst in Each Other. Issue 1 (March 2019) - Finkel, Eli J.
A major idea in relationship science is that partners in a close relationship can "sculpt" each other in a manner that helps them align more closely with their ideal, or true, self. This sculpting metaphor is compelling, elegant, and generative, but it also possesses previously unrecognized liabilities, especially in its conceptualization of the ideal self as a sculpture yearning for release from a block of stone that is imprisoning it. Given the powerful role that metaphors play in structuring thought, overreliance on the sculpting metaphor has blinded us to certain questions even as it has sensitized us to others. To develop a comprehensive understanding of the ways in which relationship partners bring out the best or the worst in each other, we must complement the sculpting metaphor with metaphors that direct our attention to questions that it obscures, such as (a) where the ideal self comes from and (b) whether, how much, and how the ideal self changes over time.